Evaluation of Knowledge, Attitudes and Experience of off-label Drug Prescribing Practice among Physicians in Baghdad City Hospitals - Shanshal, Aysha M.; H. Ataimish, Ahmed (Iraqi Journal of Pharmaceutical Sciences, 2019)
Abstract The present study aims to assess the knowledge, attitude, and experience of off-label prescribing practice among physicians in Baghdad city hospitals. This cross-sectional study was performed through the period from November 1st 2018 to March 2019 at 17 hospitals, a self-administered questionnaire was utilized to collect data from the physicians, and the targeted hospitals were randomly selected at different regions in Baghdad City area. Out of the 400 distributed questionnaires to the physicians, 383 of them were returned completed, 57.2% indicated that they were reasonably familiar with the term “off label drug”, 57.7% mentioned that the most common medical reasons for the prescribing off-label drugs were unavailability of alternatives, 67.6%, 65.5% had concerns regarding its safety and efficacy respectively, 62.7% agreed that the (MOH) authority should provide an incentive to stimulate pharmaceutical companies to perform clinical trials in Iraqi patients, 49.1% believed that clinical trials that recruit volunteers involve ethical issues. Extensive efforts are required to implant programs, regulations and guidelines to control the off-label prescribing practice among the Iraqi healthcare providers who are authorized to prescribe medications at different healthcare settings.